Water Level Sensor Berbasis Arduino UNO R3 - Akmal Aziz; Muhammad Subhan Aditya; Sandi Rahyadi; Apipah Apipah; Zada Aulia Munawarah; Didik Aribowo (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The availability of clean water is essential in daily life and plays an important role in agriculture, industry, and households. Water resource management faces many challenges such as fluctuations that can cause waste and shortages. The purpose of this research is to create a device that can automatically monitor water surface levels. The tool in question is a water level sensor based on Arduino Uno, which consists of a water level sensor and an Arduino Uno microcontroller. The sensor technology on Arduino can effectively monitor water usage directly and is known for its ease of use, flexibility, and sensor compatibility. An efficient water monitoring system provides accurate information about water availability.